Uwarunkowania przedsiębiorczości osób niepełnosprawnych w teorii i w praktyce - Woźniak, Agnieszka (Entrepreneurship Conditionality and the Disabled People. Theory and Practice, 2009)
This article includes a review of conditionality forming entrepreneurship managed by the disabled. Their character is that of factors of endo- and egzogenic nature. They include those supporting the enterprising process and its results, as well as those which inhibit this process. (original abstract)
Prace Naukowe Uniwersytetu Ekonomicznego we Wrocławiu = Research Papers of Wrocław University of Economics; 2009; Nr 39, T. 1, s. 887-894